PENGARUH FAKTOR LATAR BELAKANG PENDIDIKAN TERHADAP KUALITAS LAPORAN KEUANGAN MELALUI PENEGTAHUAN AKUNTANSI SEBAGAI VARIABEL INTERVENING - Putri, Anastasya Herwinanti Kusuma (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2017)
This study aims to provide empirical evidence that educational backgrounds affect the knowledge of accounting. As well as accounting knowledge affect the quality of financial statements. This study uses purposive sampling, where the sample is the owner of the existing SMALL MEDIUM ENTERPRISE business in the city of Surabaya. The questionnaire used in this study to collect data, and data in the analysis using Smart PLS (Partial Lease Square). The results of this study indicate the influence of educational background on accounting knowledge and the influence of accounting knowledge on the quality of financial statements. Based on the results of research and limitations of research that has been described above, it can suggest the following accounting knowledge for entrepreneurs SMALL MEDIUM ENTERPRISE very useful for the development and progress of business.